Laminated slab and preparation method thereof

By using limestone powder, slag, silica fume and other materials in the laminated plate to slurry strengthen the regenerated coarse aggregate, and combining specific fine aggregates and fiber yarns, the problem of poor quality of regenerated coarse aggregate concrete in the laminated plate is solved. , achieving high strength, high toughness and ease of concrete preparation.

CN119427850AInactive Publication Date: 2025-02-14SHAANXI TIANLI HENGTAI NEW BUILDING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510034146.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The use of reclaimed coarse aggregate concrete in existing laminates has problems such as low stacking density, high water absorption, increased crushing indicators and strong complexity in the interface transition zone, resulting in poor quality of laminates.

Method used

Limestone powder and slag part are used instead of cement, silica fume is used to slurry strengthen the recycled coarse aggregate and iron ore waste, combining machined sand, fine river sand, basalt fiber textile yarn and specific admixtures (such as modified polycarboxylic acids) Water reducing agent, viscosity regulator, defoaming agent), and concrete with high compressive strength and split strength are prepared.

Benefits of technology

The compressive strength, split strength, equivalent bending strength and toughness index of the laminated plate are improved, and the ease of concrete and pumpability are enhanced, and the risk of cracking is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427850A_ABST
    Figure CN119427850A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of laminated slabs, and particularly discloses a laminated slab and a preparation method thereof. The laminated slab comprises a prefabricated layer, a steel reinforcement framework and a laminated layer, the reinforcement cage is located in the prefabricated layer, a grid-shaped groove is formed in one side of the prefabricated layer, the laminated layer is formed by pouring concrete on one side of the grid-shaped groove, the concrete adopts limestone powder and slag to partially replace cement, and silica fume is used for carrying out slurry wrapping reinforcement on recycled coarse aggregate and iron ore waste rock. Machine-made sand and fine river sand are used as fine aggregates, basalt fiber textile yarns are added as reinforcing ribs, and finally additives such as a viscosity modifier and a modified polycarboxylate superplasticizer are added, so that the concrete is prepared. The prepared concrete has the advantages of good workability, strong pumpability, high compressive strength and splitting tensile strength, and large equivalent bending strength ratio and toughness index, and is suitable for preparation of laminated slabs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of laminated boards, and more specifically, to a laminated board and a method for preparing the same. Background Art

[0002] For a long time, concrete structure construction has been mainly based on on-site pouring, with extensive construction methods, unstable quality, low efficiency, long cycle and other problems. At the same time, the demand for formwork is high and a large amount of waste is generated, which does not meet the needs of green and efficient social and economic development. In order to improve the level of integration of building industrialization technology and improve construction quality, prefabricated buildings are vigorously promoted. The composite slab is an important component in prefabricated buildings.

[0003] Recycled coarse aggregate for concrete used in composite slabs refers to particles with a particle size greater than 4.75 mm that are processed from concrete, stone, brick, tile, etc. from construction waste and used to prepare concrete. Recycled aggregate concrete refers to concrete mixed with recycled aggregate. Recycling waste concrete as recycled aggregate can reduce the over-exploitation and damage to the natural environment caused by the production of building materials raw materials, effectively solve the problem of the accumulation and treatment of construction waste, and is an economical and environmentally friendly green production method.

[0004] However, in the current research and application of solid waste recycling to prepare coarse aggregate, the more commonly used raw materials are concrete fragments. Its surface contains more sand and has sharp edges and corners, the outer layer of old mortar is unevenly wrapped, and there are a large number of microcracks distributed inside, which are easy to produce new fracture surfaces. It is generally believed that the bulk density of recycled coarse aggregate made from discarded concrete fragments is lower than that of ordinary coarse aggregate, and its surface is rougher and the porosity is higher, resulting in a corresponding increase in water absorption and crushing index. The recycled concrete prepared by it will also produce a more complex and lower strength interface transition zone. The microcracks generated by recycled concrete when subjected to stress first appear in this range and continue to expand. Therefore, when using relevant materials to prepare concrete, the aggregate and concrete should be strengthened and modified to reduce the adverse effects of the initial defects contained in it on the performance of concrete. In addition, the use of recycled coarse aggregate will also cause the occurrence of phenomena such as water seepage and segregation in recycled concrete, which will lead to a significant decrease in the pumpability of the concrete mixture and poor quality of the composite board. Summary of the invention

[0005] In order to further improve the quality of a laminated board, the present application provides a laminated board and a method for preparing the same.

[0006] In a first aspect, the present application provides a laminated board, which adopts the following technical solution: A composite board comprises a prefabricated layer, a steel bar skeleton and a composite board; the steel bar skeleton is located in the prefabricated layer, one side of the prefabricated layer is provided with a grid-shaped groove, and the composite board is formed by pouring concrete on one side of the grid-shaped groove; the concrete comprises the following components by weight: 200-250 parts of cement, 30-50 parts of limestone powder, 50-80 parts of slag, 50-80 parts of silica fume, 600-800 parts of recycled coarse aggregate, 550-650 parts of iron ore waste rock, 450-600 parts of machine-made sand, 250-300 parts of fine river sand, 80-140 parts of basalt fiber textile yarn, 8-12 parts of admixture, and 150-180 parts of water; the admixture comprises 5-7 parts of modified polycarboxylic acid water reducer, 2-3 parts of viscosity regulator, and 1-2 parts of defoamer.

[0007] By adopting the above technical scheme, limestone powder and slag are used to partially replace cement, silica fume is used to coat and strengthen recycled coarse aggregate and iron ore waste rock, machine-made sand and fine river sand are used as fine aggregate, basalt fiber textile yarn is added as reinforcing bar, and finally admixtures such as viscosity regulator and modified polycarboxylic acid water reducer are added to prepare concrete. The prepared concrete has the advantages of good workability and strong pumpability, high compressive strength and splitting tensile strength, and large equivalent bending strength ratio and toughness index.

[0008] Preferably, the average particle size of the machine-made sand is 0.5-1 mm; the average particle size of the fine river sand is 0.2-0.3 mm.

[0009] By adopting the above technical solution, machine-made sand and fine river sand with this particle size are used as fine aggregate, which is conducive to replacing river sand with machine-made sand, enabling more cement to absorb admixtures and improving the fluidity of concrete.

[0010] Preferably, the specific surface area of ​​the limestone powder is 650m 2 / kg; the specific surface area of ​​the slag is 450m 2 / kg; the specific surface area of ​​the silica fume is 21m 2 / g.

[0011] By adopting the above technical solution, adding limestone powder and slag with this specific surface area can improve the initial working performance and collapse resistance of concrete, and increase the compressive strength and flexural strength of concrete.

[0012] Preferably, the average particle size of the recycled coarse aggregate is 18-25 mm.

[0013] By adopting the above technical solution and using recycled coarse aggregate within this particle size range, it is beneficial to improve the mechanical properties and durability of concrete.

[0014] Preferably, the monofilament diameter of the basalt fiber textile yarn is 5.5um-10um, and the length is 20mm-50mm.

[0015] By adopting the above technical solution, the basalt fiber textile yarn of this specification is beneficial to increasing the splitting tensile strength, equivalent bending strength ratio and toughness index of concrete.

[0016] Preferably, the viscosity regulator is a 0.2-0.5 g / mL aqueous solution of konjac glucomannan.

[0017] By adopting the above technical solution, using the konjac glucomannan aqueous solution at this concentration as a viscosity regulator is beneficial to improving the mixing performance of concrete.

[0018] Preferably, the defoamer is a silicone defoamer.

[0019] Preferably, the preparation method of the modified polycarboxylic acid water reducer is as follows: S1, under a nitrogen atmosphere, ethylene glycol monovinyl polyethylene glycol ether is mixed with deionized water, stirred and dissolved at 60-70°C, then trifluoromethanesulfonic acid is slowly added, the temperature is raised to 90-100°C, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane is slowly added while stirring, refluxed and stirred for reaction for 10-12h, and then reduced pressure distillation is performed to obtain a silane-modified polyether; S2, silane-modified polyether, ethylene glycol monovinyl polyethylene glycol ether, 30wt% hydrogen peroxide and water are uniformly mixed, then heated to 50-60°C, and a droplet of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, mercaptoethanol and water is added dropwise while stirring, and after the addition is completed, the stirring reaction is continued for 1-1.5h, and finally the pH value is adjusted to 6-7 to obtain a modified polycarboxylic acid water reducer.

[0020] By adopting the above technical scheme, ethylene glycol monovinyl polyethylene glycol ether is subjected to terminal ring-opening silane modification with β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, and then polymerized with ethylene glycol monovinyl polyethylene glycol ether, acrylic acid and hydroxypropyl methacrylate to prepare a modified polycarboxylic acid water reducer. Compared with conventional polycarboxylic acid water reducers, the modified polycarboxylic acid water reducer has better dispersibility and dispersion retention, and can improve the mixing performance of concrete and the later mechanical properties of concrete by adding it together with konjac glucomannan aqueous solution.

[0021] Preferably, the amount ratio of ethylene glycol monovinyl polyethylene glycol ether, deionized water, trifluoromethanesulfonic acid, and β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane in S1 is (1-1.2) mol: (10-12) mL: (2-2.5) mol: (1-1.5) mol; the amount ratio of silane-modified polyether, ethylene glycol monovinyl polyethylene glycol ether, 30 wt% hydrogen peroxide, water, and dropping liquid in S2 is: (0 .2-0.4) mol: (0.6-1) mol: (15-20) mL: (10-15) mL: (20-30) mL; the dosage ratio of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, 3-mercaptopropanol and water in the dropwise solution is (1.6-3) mol: (1.2-2.8) mol: (0.12-0.15) mol: (0.4-0.8) mol: (12-18) mL.

[0022] By adopting the above technical solution, the modified polycarboxylic acid water-reducing agent has the best dispersibility.

[0023] In a second aspect, the present application provides a method for preparing a composite board, comprising the following steps: (1) adding a modified polycarboxylic acid water reducer, a defoaming agent and a viscosity regulator to one-third of the mass of water, stirring evenly to obtain a mixed solution; (2) adding silica fume to the remaining water, mixing evenly, then adding recycled coarse aggregate and iron ore waste rock and continuing to stir, then adding cement, slag, limestone powder, machine-made sand, fine river sand and basalt chopped fibers, slowly adding the mixed solution while stirring to obtain concrete; (3) applying an interface agent to the mold, tying a steel cage in the mold, then pouring and smoothing the concrete in the mold, then pressing a grid-shaped groove on the surface, curing at room temperature for 24-28 hours, then demolding, and curing at room temperature for 25-30 days to obtain a prefabricated layer; (4) pouring concrete onto one side of the prefabricated layer having a grid-shaped groove, steam curing for 20-24 hours, and then curing under standard curing conditions for 40-48 hours to obtain a composite board.

[0024] By adopting the above technical solution, silica fume has the best chemical strengthening effect on recycled coarse aggregate.

[0025] In summary, this application has the following beneficial effects: 1. The present application adopts limestone powder and slag to partially replace cement, uses silica fume to coat recycled coarse aggregate and iron ore waste rock for slurry reinforcement, uses machine-made sand and fine river sand as fine aggregate, adds basalt fiber textile yarn as reinforcing bar, and finally adds viscosity regulator and modified polycarboxylic acid water reducer and other admixtures to prepare concrete. The prepared concrete has the advantages of good workability and strong pumpability, high compressive strength and splitting tensile strength, and large equivalent bending strength ratio and toughness index.

[0026] 2. In the present application, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane is preferably used to carry out terminal ring-opening silane modification of ethylene glycol monovinyl polyethylene glycol ether, and then polymerized with ethylene glycol monovinyl polyethylene glycol ether, acrylic acid and hydroxypropyl methacrylate to prepare a modified polycarboxylic acid water reducer. Compared with conventional polycarboxylic acid water reducers, the modified polycarboxylic acid water reducer has better dispersibility and dispersion retention, and adding it together with konjac glucomannan aqueous solution can improve the mixing performance of concrete and improve the later mechanical properties of concrete.

[0027] 3. The composite plate prepared by the preparation method of the present application has high compressive strength and splitting strength, large equivalent bending strength ratio and toughness index, and is not easy to crack. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : Infrared spectrum of the modified polycarboxylate water-reducing agent of the present application.

[0029] Figure 2 : SEM images of the concrete prepared in the present application, wherein (a) is Comparative Example 2 (×500), (b) is Example 2 (×500), (c) is Comparative Example 2 (×1500), and (d) is Example 2 (×1500). DETAILED DESCRIPTION

[0030] The present application is further described in detail below with reference to the embodiments.

[0031] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0032] Example 1 A composite board comprises a prefabricated layer, a steel bar skeleton and a composite board; the steel bar skeleton is located in the prefabricated layer, a grid-type groove is provided on one side of the prefabricated layer, and the composite board is formed by pouring concrete on one side of the grid-type groove; the concrete comprises the following components by weight: 200 parts of cement, 30 parts of limestone powder, 50 parts of slag, 50 parts of silica fume, 600 parts of recycled coarse aggregate, 550 parts of iron ore waste rock, 450 parts of machine-made sand, 250 parts of fine river sand, 80 parts of basalt fiber textile yarn, 8 parts of admixture, and 150 parts of water; the admixture comprises 5 parts of modified polycarboxylic acid water reducer, 2 parts of viscosity regulator, and 1 part of defoamer.

[0033] The average particle size of the machine-made sand is 0.5 mm; the average particle size of the fine river sand is 0.2 mm.

[0034] The specific surface area of ​​the limestone powder is 650m 2 / kg; the specific surface area of ​​the slag is 450m 2 / kg; the specific surface area of ​​the silica fume is 21m 2 / g.

[0035] The average particle size of the recycled coarse aggregate is 18 mm.

[0036] The monofilament diameter of the basalt fiber textile yarn is 5.5um and the length is 20mm.

[0037] The viscosity regulator is a 0.2 g / mL konjac glucomannan aqueous solution.

[0038] The defoamer is an organosilicon defoamer.

[0039] The preparation method of the modified polycarboxylate water-reducing agent is: S1, under nitrogen atmosphere, 1 mol of ethylene glycol monovinyl polyethylene glycol ether was mixed with 10 mL of deionized water, stirred and dissolved at 60°C, then 2 mol of trifluoromethanesulfonic acid was slowly added, the temperature was raised to 90°C, 1 mol of β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane was slowly added while stirring, the reaction was refluxed and stirred for 10 h, and then vacuum distilled to obtain silane-modified polyether; S2, 0.2 mol of silane-modified polyether, 0.6 mol of ethylene glycol monovinyl polyethylene glycol ether, 15 mL of 30 wt% hydrogen peroxide and 10 mL of water are mixed evenly, then the temperature is raised to 50°C, and 20 mL of a dropping solution consisting of a uniform mixture of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, mercaptoethanol and water is slowly added dropwise while stirring. After the addition is completed, the stirring reaction is continued for 1 hour, and finally the pH value is adjusted to 6 to obtain a modified polycarboxylic acid water-reducing agent; the amount ratio of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, 3-mercaptopropanol and water in the dropping solution is 1.6 mol:1.2 mol:0.12 mol:0.4 mol:12 mL.

[0040] The prepared modified polycarboxylate water reducer was subjected to infrared testing, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that 3412cm -1 The stretching vibration peak of hydroxyl group is 2821cm -1 The stretching vibration peaks of the subunit and methylene are at 1761cm -1 The stretching vibration peak of the carbon-oxygen double bond of carboxylic acid is at 1162 cm -1 The characteristic absorption peak of dialkyl ether carbon oxygen carbon is 1082cm -1 The characteristic absorption peak of siloxane is 821cm -1 The peak at the center is the stretching vibration absorption peak of the carbon-silicon bond, which shows that the polycarboxylic acid water-reducing agent has been successfully modified.

[0041] A method for preparing a composite board comprises the following steps: (1) adding a modified polycarboxylic acid water reducer, a defoamer and a viscosity regulator to one third of the mass of water, stirring evenly to obtain a mixed solution; (2) adding silica fume to the remaining water, mixing evenly, then adding recycled coarse aggregate and iron ore waste rock and continuing to stir, then adding cement, slag, limestone powder, machine-made sand, fine river sand and basalt chopped fibers, slowly adding the mixed solution while stirring to obtain concrete; (3) applying an interface agent to a mold, tying a steel cage in the mold, then pouring and smoothing concrete in the mold, then pressing a grid-shaped groove on the surface, curing at room temperature for 24 hours, then demoulding, and curing at room temperature for 25 days to obtain a prefabricated layer; (4) pouring concrete onto one side of the prefabricated layer having the grid-shaped groove, steam curing for 20 hours, and then curing under standard curing conditions for 40 hours to obtain a composite board.

[0042] Example 2 A composite board comprises a prefabricated layer, a steel bar skeleton and a composite board; the steel bar skeleton is located in the prefabricated layer, a grid-shaped groove is provided on one side of the prefabricated layer, and the composite board is formed by pouring concrete on one side of the grid-shaped groove; the concrete comprises the following components by weight: 230 parts of cement, 40 parts of limestone powder, 65 parts of slag, 68 parts of silica fume, 700 parts of recycled coarse aggregate, 600 parts of iron ore waste rock, 520 parts of machine-made sand, 280 parts of fine river sand, 110 parts of basalt fiber textile yarn, 10 parts of admixture, and 165 parts of water; the admixture comprises 6 parts of modified polycarboxylic acid water reducer, 3 parts of viscosity regulator, and 2 parts of defoamer.

[0043] The average particle size of the machine-made sand is 0.8 mm; the average particle size of the fine river sand is 0.3 mm.

[0044] The specific surface area of ​​the limestone powder is 650m 2 / kg; the specific surface area of ​​the slag is 450m 2 / kg; the specific surface area of ​​the silica fume is 21m 2 / g.

[0045] The average particle size of the recycled coarse aggregate is 20 mm.

[0046] The monofilament diameter of the basalt fiber textile yarn is 7.5um and the length is 35mmmm.

[0047] The viscosity regulator is a 0.4 g / mL konjac glucomannan aqueous solution.

[0048] The defoamer is an organosilicon defoamer.

[0049] The preparation method of the modified polycarboxylate water-reducing agent is: S1, under nitrogen atmosphere, 1.1 mol of ethylene glycol monovinyl polyethylene glycol ether was mixed with 11 mL of deionized water, stirred and dissolved at 65°C, then 2.3 mol of trifluoromethanesulfonic acid was slowly added, the temperature was raised to 95°C, 1.2 mol of β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane was slowly added while stirring, the reaction was refluxed and stirred for 11 h, and then vacuum distilled to obtain silane-modified polyether; S2, 0.3 mol of silane-modified polyether, 0.8 mol of ethylene glycol monovinyl polyethylene glycol ether, 18 mL of 30 wt% hydrogen peroxide and 12 mL of water are mixed evenly, then the temperature is raised to 55°C, and 25 mL of a dropping solution consisting of a uniform mixture of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, mercaptoethanol and water is slowly added dropwise while stirring. After the addition is completed, the reaction is continued with stirring for 1.5 h, and the pH value is finally adjusted to 7 to obtain a modified polycarboxylic acid water-reducing agent; the amount ratio of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, 3-mercaptopropanol and water in the dropping solution is 2.4 mol:2.2 mol:0.14 mol:0.6 mol:15 mL.

[0050] A method for preparing a composite board comprises the following steps: (1) adding a modified polycarboxylic acid water reducer, a defoamer and a viscosity regulator to one third of the mass of water, stirring evenly to obtain a mixed solution; (2) adding silica fume to the remaining water, mixing evenly, then adding recycled coarse aggregate and iron ore waste rock and continuing to stir, then adding cement, slag, limestone powder, machine-made sand, fine river sand and basalt chopped fibers, slowly adding the mixed solution while stirring to obtain concrete; (3) applying an interface agent to a mold, tying a steel cage in the mold, then pouring and smoothing concrete in the mold, then pressing a grid-shaped groove on the surface, curing at room temperature for 26 hours, then demoulding, and curing at room temperature for 28 days to obtain a prefabricated layer; (4) pouring concrete onto one side of the prefabricated layer having the grid-shaped groove, steam curing for 22 hours, and then curing under standard curing conditions for 44 hours to obtain a composite board.

[0051] Example 3 A composite board comprises a prefabricated layer, a steel bar skeleton and a composite board; the steel bar skeleton is located in the prefabricated layer, a grid-type groove is provided on one side of the prefabricated layer, and the composite board is formed by pouring concrete on one side of the grid-type groove; the concrete comprises the following components by weight: 250 parts of cement, 50 parts of limestone powder, 80 parts of slag, 80 parts of silica fume, 800 parts of recycled coarse aggregate, 650 parts of iron ore waste rock, 600 parts of machine-made sand, 300 parts of fine river sand, 140 parts of basalt fiber textile yarn, 12 parts of admixture, and 180 parts of water; the admixture comprises 7 parts of modified polycarboxylic acid water reducer, 3 parts of viscosity regulator, and 1 part of defoamer.

[0052] The average particle size of the machine-made sand is 1 mm; the average particle size of the fine river sand is 0.3 mm.

[0053] The specific surface area of ​​the limestone powder is 650m 2 / kg; the specific surface area of ​​the slag is 450m 2 / kg; the specific surface area of ​​the silica fume is 21m 2 / g.

[0054] The average particle size of the recycled coarse aggregate is 25 mm.

[0055] The monofilament diameter of the basalt fiber textile yarn is 10um and the length is 50mm.

[0056] The viscosity regulator is a 0.5 g / mL konjac glucomannan aqueous solution.

[0057] The defoamer is an organosilicon defoamer.

[0058] The preparation method of the modified polycarboxylate water-reducing agent is: S1, under nitrogen atmosphere, 1.2 mol of ethylene glycol monovinyl polyethylene glycol ether was mixed with 12 mL of deionized water, stirred and dissolved at 70°C, then 2.5 mol of trifluoromethanesulfonic acid was slowly added, the temperature was raised to 100°C, 1.5 mol of β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane was slowly added while stirring, the mixture was refluxed and stirred for 12 h, and then distilled under reduced pressure to obtain silane-modified polyether; S2, 0.4 mol of silane-modified polyether, 1 mol of ethylene glycol monovinyl polyethylene glycol ether, 20 mL of 30 wt% hydrogen peroxide and 15 mL of water are mixed evenly, then the temperature is raised to 60°C, and 30 mL of a dropping solution consisting of a uniform mixture of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, mercaptoethanol and water is slowly added dropwise while stirring. After the addition is completed, the stirring reaction is continued for 1.5 h, and the pH value is finally adjusted to 7 to obtain a modified polycarboxylic acid water-reducing agent; the amount ratio of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, 3-mercaptopropanol and water in the dropping solution is 3 mol:2.8 mol:0.15 mol:0.8 mol:18 mL.

[0059] A method for preparing a composite board comprises the following steps: (1) adding a modified polycarboxylic acid water reducer, a defoamer and a viscosity regulator to one third of the mass of water, stirring evenly to obtain a mixed solution; (2) adding silica fume to the remaining water, mixing evenly, then adding recycled coarse aggregate and iron ore waste rock and continuing to stir, then adding cement, slag, limestone powder, machine-made sand, fine river sand and basalt chopped fibers, slowly adding the mixed solution while stirring to obtain concrete; (3) applying an interface agent to a mold, tying a steel cage in the mold, then pouring and smoothing concrete in the mold, then pressing a grid-shaped groove on the surface, curing at room temperature for 28 hours, then demoulding, and curing at room temperature for 30 days to obtain a prefabricated layer; (4) pouring concrete onto one side of the prefabricated layer having the grid-shaped groove, steam curing for 24 hours, and then curing under standard curing conditions for 48 hours to obtain a composite board.

[0060] Comparative Example 1 The same as Example 2, except that no konjac glucomannan aqueous solution was added.

[0061] Comparative Example 2 The same as Example 2, except that the same mass of polycarboxylic acid-based high-performance water reducer (purchased from Shandong Yuncheng Huihuang New Building Materials Technology Co., Ltd.) was used instead of the modified polycarboxylic acid water reducer.

[0062] Comparative Example 3 The same as Example 2, except that in a method for preparing a composite board, (2) the following steps are performed: recycled coarse aggregate and iron ore waste rock are added to the remaining water, and then cement, slag, limestone powder, silica fume, machine-made sand, fine river sand and basalt chopped fibers are added, and the mixture is slowly added while stirring to obtain concrete.

[0063] Comparative Example 4 Same as Example 2, except that the basalt fiber textile yarn is replaced with steel fiber of the same mass.

[0064] Performance testing 1. Determine the slump, expansion and emptying time of the concrete prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4 at the initial stage and at 30 minutes; specifically: moisten the iron plate and the inner wall of the slump cone, pour the concrete into the slump cone three times, tamp it 30 times with a tamping rod, pour 1 / 3 of the cone height each time, smooth the surface, lift the slump cone, and after it stops flowing on the iron plate, test the slump and expansion diameter (i.e. expansion). Moisten the iron plate and the inner wall of the slump cone, pour the concrete into the inverted slump cone twice, tamp it 15 times with a tamping rod each time, and quickly lift the slump cone after smoothing the surface, and record the time it takes to be completely emptied. Repeat three times and take the average value. The results are shown in Table 1: Table 1 Concrete slump test results

[0065] As can be seen from Table 1, the initial expansion of the concrete prepared by Examples 1 to 3 of the present application is between 610 and 627 mm, the initial slump is between 242 and 269 mm, the 30 min expansion is between 553 and 561 mm, the initial slump is between 221 and 225 mm, the ratio of slump to expansion is about 0.4, and the emptying time is short, indicating that the prepared concrete has good workability and strong pumpability; in conjunction with Comparative Examples 1-4, it can be seen that the konjac glucomannan aqueous solution, the modified polycarboxylic acid water-reducing agent and the mixing method have a greater impact on its workability and pumpability, while the selection of fiber has substantially no effect on it.

[0066] 2. The concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was prepared into specimens of 100 mm × 100 mm × 100 mm, steam-cured for 24 h, and then cured for 7 d and 28 d under standard curing conditions. The 7d and 28d compressive strength (loading rate of 1.2 MPa / s) and 7d and 28d splitting tensile strength (loading rate of 0.1 MPa / s) of the concrete were measured according to GB / T50107-2019; the concrete was prepared into specimens of 100 mm × 100 mm × 400 mm, and then its equivalent flexural strength ratio and toughness index were measured according to ASTMC1609.

[0067] The results are shown in Table 2: Table 2 Test results of concrete mechanical properties

[0068] As can be seen from Table 2, the concrete prepared by Examples 1 to 3 of the present application has higher 7d and 28d compressive strength and splitting strength, and higher equivalent bending strength ratio and toughness index, indicating that the prepared concrete has excellent mechanical properties; in combination with Comparative Examples 1 to 4, it can be seen that the konjac glucomannan aqueous solution, modified polycarboxylate water-reducing agent, mixing method and fiber selection all have a certain influence on its mechanical properties, among which the modified polycarboxylate water-reducing agent has the greatest influence on the compressive strength, and the fiber selection has the greatest influence on the splitting strength, equivalent bending strength ratio and toughness index.

[0069] 3. Based on the solutions of Example 2 and Comparative Example 2, for the convenience of observation, no basalt fiber textile yarn was added, and then concrete was prepared. The microscopic morphology of the prepared concrete was observed using a scanning electron microscope at 7 days. The results are as follows: Figure 2 As shown. Figure 2 It can be seen from (a) and (c) that the hydration product structure of the concrete prepared in Comparative Example 2 is relatively loose and the compactness of the concrete is poor. Figure 2It can be seen from (b) and (d) that the structure of the hydration product of the concrete prepared in Example 2 is relatively dense, and the concrete has high compactness. Therefore, it can be seen that the modified polycarboxylate water-reducing agent in the present application can improve the cohesiveness and water retention of concrete, improve the compactness of concrete mixtures, and improve the later strength of concrete.

[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A composite board, characterized in that: It comprises a prefabricated layer, a steel skeleton and a laminated layer; the steel skeleton is located in the prefabricated layer, one side of the prefabricated layer is provided with a grid-type groove, and the laminated layer is formed by pouring concrete on one side of the grid-type groove; the concrete comprises the following components by weight: 200-250 parts of cement, 30-50 parts of limestone powder, 50-80 parts of slag, 50-80 parts of silica fume, 600-800 parts of recycled coarse aggregate, 550-650 parts of iron ore waste rock, 450-600 parts of machine-made sand, 250-300 parts of fine river sand, 80-140 parts of basalt fiber textile yarn, 8-12 parts of admixture, and 150-180 parts of water; the admixture comprises 5-7 parts of modified polycarboxylic acid water reducer, 2-3 parts of viscosity regulator, and 1-2 parts of defoamer.

2. A composite board according to claim 1, characterized in that: The average particle size of the machine-made sand is 0.5-1 mm; the average particle size of the fine river sand is 0.2-0.3 mm.

3. A composite board according to claim 2, characterized in that: The specific surface area of ​​the limestone powder is 650m 2 / kg; the specific surface area of ​​the slag is 450m 2 / kg; the specific surface area of ​​the silica ash is 21m 2 / g.

4. A composite board according to claim 3, characterized in that: The average particle size of the recycled coarse aggregate is 8-20 mm.

5. A composite board according to claim 4, characterized in that: The monofilament diameter of the basalt fiber textile yarn is 5.5um-10um, and the length is 20mm-50mm.

6. A composite board according to claim 5, characterized in that: The viscosity regulator is a 0.2-0.5 g / mL konjac glucomannan aqueous solution.

7. A composite board according to claim 6, characterized in that: The defoamer is an organosilicon defoamer.

8. A composite board according to claim 7, characterized in that: The preparation method of the modified polycarboxylic acid water-reducing agent is as follows: S1, in a nitrogen atmosphere, ethylene glycol monovinyl polyethylene glycol ether is mixed with deionized water, stirred and dissolved at 60-70° C., then trifluoromethanesulfonic acid is slowly added, the temperature is raised to 90-100° C., β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane is added while stirring, reflux and stir to react for 10-12 hours, and then reduced pressure distillation is performed to obtain silane-modified polyether; S2, silane-modified polyether, ethylene glycol monovinyl polyethylene glycol ether, 30wt% hydrogen peroxide and water are uniformly mixed, then the temperature is raised to 50-60° C., and a drop solution consisting of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, mercaptoethanol and water is dripped while stirring, after the dripping is completed, the stirring reaction is continued for 1-1.5 hours, and finally the pH value is adjusted to 6-7 to obtain the modified polycarboxylic acid water-reducing agent.

9. A composite board according to claim 8, characterized in that: The dosage ratio of ethylene glycol monovinyl polyethylene glycol ether, deionized water, trifluoromethanesulfonic acid, and β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane is (1-1.2) mol: (10-12) mL: (2-2.5) mol: (1-1.5) mol; the dosage ratio of silane-modified polyether, ethylene glycol monovinyl polyethylene glycol ether, 30 wt% hydrogen peroxide, water, and dropping liquid is: (0.2-0. 4) mol: (0.6-1) mol: (15-20) mL: (10-15) mL: (20-30) mL; the dosage ratio of acrylic acid, hydroxypropyl methacrylate, ascorbic acid, 3-mercaptopropanol and water in the dropwise addition liquid is (1.6-3) mol: (1.2-2.8) mol: (0.12-0.15) mol: (0.4-0.8) mol: (12-18) mL.

10. A method for preparing a laminated board according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) adding a modified polycarboxylic acid water reducer, a defoamer and a viscosity regulator to one third of the mass of water, stirring evenly to obtain a mixed solution; (2) adding silica fume to the remaining water, mixing evenly, then adding recycled coarse aggregate and iron ore waste rock and continuing to stir, then adding cement, slag, limestone powder, machine-made sand, fine river sand and basalt chopped fibers, slowly adding the mixed solution while stirring to obtain concrete; (3) applying an interface agent to the mold, tying a steel cage in the mold, then pouring and smoothing the concrete in the mold, then pressing a grid-shaped groove on the surface, curing at room temperature for 24-28 hours, then demolding, and curing at room temperature for 25-30 days to obtain a prefabricated layer; (4) pouring concrete onto one side of the prefabricated layer having the grid-shaped groove, steam curing for 20-24 hours, and then curing under standard curing conditions for 40-48 hours to obtain a composite board.

Citation Information

Patent Citations

  • Early-strength polycarboxylate superplasticizer and preparation method thereof

    CN111348858A

  • Solid waste large-mixing-amount concrete prefabricated laminated slab and preparation method thereof

    CN112757437A

  • Shrinkage reducing agent as well as preparation method and application thereof

    CN115403712A

  • Stabilization treatment method for waste incineration fly ash

    CN115784668A

  • Laminated plywood

    JP2006015613A